Electrical and optical properties of Sb-doped BaSnO3 - Mizoguchi, Hiroshi; Chen, Ping; Boolchand, Punit; Ksenofontov, Vadim; Felser, Claudia; Barnes, Paris W.; Woodward, Patrick M. (Chemistry of Materials, 2013)
The electronic and optical properties of the cubic perovskite, BaSnO 3, are compared with the well-known transparent conducting oxides (TCOs), SnO2 and In2O3. The optical band gaps of the undoped compounds, as measured by diffuse reflectance spectroscopy on powdered samples, are 3.1 eV for BaSnO3 and 3.8 eV for SnO 2. Electronic structure calculations show that both compounds possess a large conduction band dispersion, which suggests that BaSnO3, like SnO2, should be a good TCO if it can be n-doped. To explore this possibility the properties of substitutionally doped, BaSn1-xSb xO3 samples were investigated. The electrical conductivity increases drastically for BaSn1-xSbxO3 samples with x ≤ 0.05, showing a transition from an insulating to a metallic state. For higher doping levels, 0.05 < x < 0.15, the conductivity saturates at 4 S cm-1. This is accompanied by saturation in the expansion of the cubic lattice parameter. The color of the pellets changed from white (x = 0) to bluish black (x = 0.15). This darkening originates from the formation of an intense and broad optical absorption band centered at 1200-1300 nm for the more highly doped samples. This absorption band spans both the visible and the near-infrared regions, resulting in a loss of transparency. Various spectroscopic techniques were used to elucidate the observed behavior. Mössbauer spectroscopy reveals the presence of mixed valent antimony, Sb3+(5s2)/Sb5+(5s0), as x increases. ESR spectra collected on a BaSn0.99Sb0.01O3 sample indicate that only ∼5% of unpaired electrons are present as delocalized carriers. The other 95% are localized to form a Sn3+ trapped electron center. To explain the tendency for carrier localization in doped BaSnO3 a mechanism based on strong electron-phonon interactions in perovskites containing cations with (n - 1)d10ns0 electronic configuration is proposed. This mechanism explains why BaSn 1-xSbxO3 possesses relatively poor TCO characteristics, in sharp contrast to widely used TCO materials Sn 1-xSbxO2 and In1-xSn xO1.5. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: mixed valence compounds; Mössbauer spectroscopy; perovskite oxides; transparent conductive oxides